2013
DOI: 10.1002/ana.23880
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNAs as biomarkers for disease staging in multiple sclerosis

Abstract: Our results establish circulating miRNAs as a readily accessible blood biomarker to monitor disease in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
196
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 232 publications
(206 citation statements)
references
References 61 publications
5
196
0
5
Order By: Relevance
“…As such, these miRNAs may be differentially expressed in other immunemediated diseases and have broader implications on CD4 T cell development and differentiation. It is well established that miRNAs play key roles in the development and function of Tregs (Gao et al, 2012;Josefowicz et al, 2012;Dooley et al, 2013), and differential expression of miRNAs have been found in patients with multiple sclerosis (Du et al, 2009;Keller et al, 2009;Otaegui et al, 2009;De Santis et al, 2010;Guerau-de-Arellano et al, 2011;Noorbakhsh et al, 2011;Jr OeF et al, 2012;Smith et al, 2012;Gandhi et al, 2013;Ridolfi et al, 2013;Søndergaard et al, 2013). To our knowledge none of the miRNAs identified in this study had been previously defined to play a role in Tregs.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…As such, these miRNAs may be differentially expressed in other immunemediated diseases and have broader implications on CD4 T cell development and differentiation. It is well established that miRNAs play key roles in the development and function of Tregs (Gao et al, 2012;Josefowicz et al, 2012;Dooley et al, 2013), and differential expression of miRNAs have been found in patients with multiple sclerosis (Du et al, 2009;Keller et al, 2009;Otaegui et al, 2009;De Santis et al, 2010;Guerau-de-Arellano et al, 2011;Noorbakhsh et al, 2011;Jr OeF et al, 2012;Smith et al, 2012;Gandhi et al, 2013;Ridolfi et al, 2013;Søndergaard et al, 2013). To our knowledge none of the miRNAs identified in this study had been previously defined to play a role in Tregs.…”
Section: Discussionmentioning
confidence: 63%
“…While genetic studies have identified genes critical to the immune system as being potential risk factors (Baranzini et al, 2009b;De Jager et al, 2009;Beecham et al, 2013), many of the genetic contributors to this disease are unknown. An emerging area of interest in multiple sclerosis has been genetic regulation at the microRNA (miRNA) level (Du et al, 2009;Keller et al, 2009;Otaegui et al, 2009;De Santis et al, 2010;Guerau-de-Arellano et al, 2011;Noorbakhsh et al, 2011;Jr OeF et al, 2012;Smith et al, 2012;Gandhi et al, 2013;Ridolfi et al, 2013;Søndergaard et al, 2013). MiRNAs are small, non-coding RNA that regulate gene expression and, thus, modify cellular pathways and disease processes (Ambros, 2004;Bartel, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21] Challenges in the analysis of circulating miRNAs include pre-analytical decisions (such as sample storage and processing) and post-analytical assessments (data normalization). 17 Detailed analyses of miRNA spectra in serum and plasma recommend plasma over serum to reduce sample-to-sample variations induced by serum coagulation, 26 and we used EDTA anticoagulated plasma in this study to avoid such variations.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Recent studies have also identified circulating miRNAs as biomarkers to monitor the disease state in T cell-mediated autoimmune diseases, such as MS and myasthenia gravis (MG). 20,21 However, miRNAs have yet to be explored in the serum or plasma of AA. The purpose of our study was to analyze the circulating miRNA profile in the plasma of AA patients and to assess whether specific miRNAs could serve as new biomarkers for AA.…”
Section: Introductionmentioning
confidence: 99%
“…Discovering a characteristic expression profile could be of key importance in the early diagnosis of MS [14,[19][20][21]. Several researchers have similarly tried to correlate the expression of certain miRNA with patients' general condition measured by the EDSS score and disease duration in patients with relapsing-remitting and secondary-progressive disease courses [19,20].…”
Section: The Stability Of Plasma Mirna and Their Use As Biomarkersmentioning
confidence: 99%